Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1968
DOI: 10.1029/wr004i005p01001
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of Stream Lengths

Abstract: Two basic assumptions are employed in this treatment of the statistics of stream lengths: (1) All topologically distinct networks with a given number of sources are equally likely (after Shreve). (2) Lengths of interior links in a given network are independent random variables drawn from the same population. The mathematical development leads to an approximate expression for L• that contains no adjustable parameters and that depends only on the stream numbers and the mean link length. This expression gives som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
3

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 11 publications
2
66
0
3
Order By: Relevance
“…Shreve 1966, 1969, Smart 1968, Kirchner 1993) have discussed Horton's and Schumm's laws on the basis of "statistical models", and they have compared the results to natural river systems. In this way, Kirchner (1993) showed that, statistically speaking, roughly 95% of river systems obey Horton's and Schumm's laws, regardless of whether the systems are topologically random or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shreve 1966, 1969, Smart 1968, Kirchner 1993) have discussed Horton's and Schumm's laws on the basis of "statistical models", and they have compared the results to natural river systems. In this way, Kirchner (1993) showed that, statistically speaking, roughly 95% of river systems obey Horton's and Schumm's laws, regardless of whether the systems are topologically random or not.…”
Section: Discussionmentioning
confidence: 99%
“…For natural catchments, the R L ratio usually ranges from 1.5 to 3.5, with the mean equal to 2.0 (Smart 1968, 1972, Bras, Rodriguez-Iturbe 1989). An R L ratio ranging from 1.5 to 3.5 was found to be typical for the large Carpathian catchments (Bajkiewicz-Grabowska 1987).…”
Section: The Length Ratio (R L )mentioning
confidence: 99%
“…[property 1] the distributions and numerical values of RB (Shreve, 1966), Rz• (Smart, 1968;Shreve, 1967Shreve, , 1969, and ( Shreve, 1969) [property 2] the correlations between RB and R L and between stream numbers and stream lengths (Smart, 1968) [property 3] the statistical distributions of second-order stream lengths, Schumm lengths, and areas (Shreve, 1969) [property 4] Meltoh's (1958) proportional relationship between stream frequency and the square of the drainage density (Shreve, 1967) [property 5] Hack's (1957) variation of mainstream length with basin area (e.g., Shreve, 1974) [property 6] Langbein et al 's (1947) relationship between distance-weighted area and basin area (Werner and Smart, 1973) [property 7] Gray's (1961) relationship between distance from outlet to "centroid" and mainstream length (Werner and Smart, 1973).…”
Section: ] (Edited)mentioning
confidence: 99%
“…For drainage networks developed under similar environmental conditions, the exterior and interior link lengths are independent random variables with a single common distribution for each type (Smart (1968) p. 1005, Shreve (1967) p. 184, (1969) p. 402)).…”
Section: Introductionmentioning
confidence: 99%